Threats to large brown algal forests in temperate seas: the overlooked role of native herbivorous fish - Fabrizio Gianni (Nature Portfolio, 2017)
Abstract Canopy-forming algae are declining globally due to multiple disturbances. This decline has recently been on the increase due to the spread of some tropical herbivorous fishes. This new phenomenon has drawn attention to the effects of fish herbivory in temperate areas, which have been assumed to be negligible compared to that of invertebrates, such as sea urchins. In this study, the impact of a Mediterranean native herbivorous fish (Sarpa salpa, salema) was assessed on the canopy-forming seaweed Cystoseira amentacea var. stricta. Cystoseira amentacea forms belts in the infralittoral fringe of wave-exposed shores, which has so far been considered a refuge from fish herbivory. To test the effects of salema feeding on natural C. amentacea belts, an innovative herbivore deterrent device was conceived. Salema had a significant effect on C. amentacea by decreasing algal size, biomass and fertility, by up to 97%. The results suggest that the contribution of salema feeding to the loss of Cystoseira forests in the Mediterranean may have been overlooked. In addition, the analysis of temporal and spatial patterns of salema landings in the Mediterranean Sea suggests that salema abundance may have increased recently. Thus, along with invertebrate herbivory and anthropogenic stressors, fish herbivory may also represent a potential threat to algal forests in temperate areas.